Development of an Adaptive Curriculum: Enhancing HOTS-Based Learning in the Classroom - Kholilur Rahman, Kholilur Rahman; Hidayah, Fathi; Wahyono, Imam; Giovany, Ananda (Universitas Nurul Jadid Probolinggo, Indonesia, 2024)
This research focuses on the development of an adaptive curriculum to enhance Higher Order Thinking Skills (HOTS)-based learning in the classroom. The aim of this study is to explore how adjustments to lesson materials, student-centered learning, the use of technology, and formative assessment can facilitate the development of HOTS in the context of secondary education. This study employs qualitative methods with a case study approach at SMAN 1 Glagah Banyuwangi. Data were collected through in-depth interviews, participatory observation, and document analysis.The findings indicate that an adaptive curriculum tailored to the needs and interests of students significantly improves student engagement and critical thinking skills. The use of technology and HOTS-based formative assessment also proved effective in supporting the development of higher-order thinking skills. These findings underscore the importance of a responsive approach to individual student needs in enhancing the quality of education. However, this study has limitations, including variations in participants and the context of the location. Therefore, further comprehensive research is recommended to expand the scope and validity of these findings. The implications of this research suggest that educational policies need to consider the implementation of adaptive curricula to more effectively and inclusively support the development of HOTS.